Islamic PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN KARAKTER DAN MORAL SISWA DI SMK NW ANJANI - Muh. Thala'at; Muhammad Ramdani Nur (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2022)
Islamic education is education that aims to guide children to have namely who are obedient and obedient to Islamic rules, as well as as a guide for their way of life. This research is a qualitative descriptive study. the problem of this research is the analysis of PAI problems on character and moral development of students. The inhibiting factor for PAI learning is the condition of the family background of most students who come from broken homes, the background of students who come from families whose parents are uneducated, so that they don't really care about children's education. The state of the community environment is very influential on the formation of students' character and morality when they are in the school environment. Students' association with school friends will not affect students who are not controlled by their parents. To overcome ms, teachers are expected to take a personal approach with students. Giving sanctions punishments to the students concerned if they violate the norms that apply. Giving spiritual showers every morning in order to meet the spiritual, coaching and self-development of students, as well as conducting yasinan, dhikr and prayer activities accompanied by lectures.